Vertical linkages and multinational plant size - Pontes, José Pedro (2009)
This paper deals with the location of input supply in a two country spatial economy. A duopoly supplies intermediate goods to a perfectly competitive consumer good industry that operates with a quadratic production function inspired in PENG, THISSE and WANG (2006). Since the consumer good is non-tradable, the downstream industry locates in both countries and can be viewed as made by a set of multinational firms. On the one hand joint location of the upstream firms is caused by a localization economy and by the intensity of the demand addressed to the industry. On the other hand production and transport costs of the input lead to dispersed locations by the upstream firms. If the input suppliers agglomerate, the neighboring downstream plant operates with a larger size that the distant one.